Three-way decisions: beyond rough sets and granular computing - Liu, Dun; Yang, Xin; Li, Tianrui (International journal of machine learning and cybernetics, 2020)
With the fast developments of three-way decisions (3WD), this paper systematically summarizes the development track and evolution process of 3WD in recent decades. Firstly, the historical context, internal connections and relations between 3WD and rough sets are carefully investigated. Then, we discuss the methodology of 3WD via granular computing with “multi-level” strategy and “multi-view” strategy. Two novel 3WD generalized models with multilevel structure and multiview structure, as well as an integration framework of multilevel and multiview, are analyzed and discussed detailedly. Finally, this paper presents the research status and future research topics of 3WD.